How did the COVID-19 pandemic affect food environment, food purchase, and fish consumption among low-income urban households in Bangladesh—A path analysis - Akter, Mahsina Syeda; Talsma, Elise F.; Feskens, Edith J. M.; Thilsted, Shakuntala H.; Rasheed, Sabrina (Frontiers in Public Health, 2022)
Background Animal source foods, especially fish is the most commonly consumed and an important source of macro and micronutrients in the diet of the urban low-income residents. The COVID-19 pandemic has disrupted the food environment in Bangladesh but little is known about how food access and food prices (affordability) have affected the purchase and consumption of fish. The objective of the study was to understand the impact of the first wave of the COVID-19 pandemic on urban food environment with a specific focus on fish consumption. Methods A cross-sectional survey was conducted among 586 homogeneous adults (288 females and 298 males) from separate households from five informal settlements in Dhaka city, Bangladesh during October-November 2020. Data were collected on: (1) food access and affordably; and (2) food purchase and fish consumption. The associations between food access, price, food purchase, and fish consumption were evaluated using path analysis. Results The majority of respondents reported that food access was more difficult, food prices increased, and food purchase decreased during the COVID-19 pandemic compared to pre-COVID (84–89% of respondents). Fish and meat were more difficult to access, more expensive and purchased less compared to other foods (74–91% of respondents). Compared to pre-COVID period, households consumed less fish during the COVID-19 pandemic, and reported compromised the variety and quality of fish. In the path analysis, food access was associated with food purchase (b = 0.33, p < 0.001). Food purchase was associated with quantity, variety, and quality of fish consumed. Food price was inversely associated with the quality of fish consumed (b = −0.27, p < 0.001). Conclusions The COVID-19 pandemic negatively affected the food environment, particularly food access, price (affordability), purchase, and consumption, especially of fish. Limited food access negatively affected the quantity, variety and quality of fish consumed. An increase in food prices directly affected the quality of fish consumed. Policy actions are essential to ensure equal access to nutritious foods, such as fish. These policies need to focus on diversity and quality along with preventing increases in food prices during emergencies to mitigate future threats to the nutrition and health of the urban low-income residents.